S90 Right ventricular remodelling assessed using cardiac magnetic resonance predicts survival and treatment response in pulmonary arterial hypertension. (11th November 2022) - Goh, ZM; Balasubramanian, N; Alabed, S; Dwivedi, K; Shahin, Y; Rothman, AMK; Garg, P; Lawrie, A; Capener, D; Thompson, AAR; Alandejani, F; Wild, JM; et al.
Abstract : Objectives: To determine the prognostic value of patterns of right ventricular (RV) adaptation in patients with pulmonary arterial hypertension (PAH), assessed using cardiac magnetic resonance (CMR) imaging at baseline and follow-up. Methods: Consecutive patients with PAH from the ASPIRE registry were included in the baseline cohort. Patients who received PAH therapy and had follow-up CMR assessment were included in the follow-up cohort. A right ventricular end-systolic volume index adjusted for age and sex (RVESVI%pred ) threshold of 227% and ventricular mass index (VMI) threshold of 0.53 were used to stratify patients into four different volume/mass groups: Vollow Masslow (low RVESVI%pred and VMI), Vollow Masshigh (low RVESVI%pred and high VMI), Volhigh Masslow (high RVESVI%pred and low VMI) and Volhigh Masshigh (high RVESVI%pred and VMI). At the baseline assessment, One-way ANOVA test and Chi-squared tests were used to compare the variables of the groups. Transition of the groups from baseline to follow-up assessment were studied and illustrated using alluvial graph. At follow-up, the prognoses of the groups were compared using Kaplan-Meier plots. Results: A total of 564 patients with PAH were identified, 250 (44.0%) died during follow-up (median 4.85 years, interquartile range 4.05). At baseline assessment, Vollow Masslow was associated with CMR and right heart catheterisation metrics predictive of improved prognosis. There were 126 patients who underwent follow up CMR (median 1.11 years, interquartile range 0.78). At both baseline and follow-up assessments, Volhigh Masslow group had worse prognosis than the Vollow Masslow group (p<0.001). At follow-up, patients with Vollow Masslow had lower mortality than Vollow Masshigh, Volhigh Masslow and Volhigh Masshigh (p<0.001). With PAH therapy, 73.5% of Vollow Masslow remained in this group, whereas 56.5% and 29.0% of Vollow Masshigh and Volhigh Masshigh patients transitioned into Vollow Masslow, respectively. In contrast, only 17.4% of Volhigh Masslow transitioned into Vollow Masslow . Conclusions: CMR can be used to assess for RV adaptation in patients with PAH and has prognostic value at baseline and follow-up. Patients with evidence of maladaptive remodelling (Volhigh Masslow ) are at high risk of treatment failure with PAH therapies and should be considered for early intensification of treatment and lung transplantation. Presence of significant RV reverse remodelling (Vollow Masslow ) at follow-up on CMR indicates good prognosis and effective treatment.